Performance Measurement of Generation Y Employees with a Human Capital Approach - Nuraeni; Hasan, Diana; Hadiati Putri Kinasih, Dini; Hafnidar, Siti (Dinasti International Journal of Economics, Finance & Accounting, 2023)
The era of globalization has resulted in several changes in views on strategic resources within a company, including human capital. Human capital is considered very important related to the company's non-financial performance. So this research tries to measure the performance of Generation Y employees with the Human Capital approach in the South Jakarta area. The aim of this research ismeasure influencehuman capitalconsisting ofindividual capability, individual motivation, the organizational climate, workgroup effectiveness,and leadership on the performance of Generation Y employees in the South Jakarta area. The method used is associative quantitative research, with the sample technique used is simple random sampling.